Are shocks actually on the rise? A selective review of five types of shocks - Zseleczky, Laura; Yosef, Sivan (International Food Policy Research Institute, 2014)
Policymakers, practitioners, and researchers frequently cite an increase in shocks around the world as a reason for focusing on resilience. But have shocks actually increased or become more severe and far‐reaching? What does the landscape of shocks look like?